1987
DOI: 10.1002/cm.970080111
|View full text |Cite
|
Sign up to set email alerts
|

Topographical relationship between the axonemal arrangement and the bend direction in starfish sperm flagella

Abstract: Since starfish spermatozoa have spherical heads, it is not easy to determine the topographical relationship of the axoneme to the directions of the flagellar bends, the principal, and the reverse bends as defined by Gibbons and Gibbons [J. Cell. Biol. 1972, 63:970-985]. The demembranated spermatozoa are known to take the quiescent "cane" shape with a sharp principal bend at the proximal region of the flagellum in the presence of high concentration of Ca2+. When such spermatozoa were placed on a grid for electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…It is therefore likely that P-bend propagating bends are generated under intermediate conditions made in the course of gradual increase in the intracellular pH. It has been demonstrated that one of potentially alternating bends propagates with the other being collapsed during the trypsin digestion in the presence of CO 2 (Brokaw and Simonick, 1977), although the propagating bend has not been identified as P or R. These findings may indicate that the axonemal structures including dynein ATPase have subtle differences in sensitivity to their environmental pH or CO 2 , resulting in selective inhibition of specific sliding between adjacent doublets required for bend generation or propagation, since the P and R bends are topographically related to the axonemal structure (Mohri et al, 1987).…”
Section: Discussionmentioning
confidence: 95%
“…It is therefore likely that P-bend propagating bends are generated under intermediate conditions made in the course of gradual increase in the intracellular pH. It has been demonstrated that one of potentially alternating bends propagates with the other being collapsed during the trypsin digestion in the presence of CO 2 (Brokaw and Simonick, 1977), although the propagating bend has not been identified as P or R. These findings may indicate that the axonemal structures including dynein ATPase have subtle differences in sensitivity to their environmental pH or CO 2 , resulting in selective inhibition of specific sliding between adjacent doublets required for bend generation or propagation, since the P and R bends are topographically related to the axonemal structure (Mohri et al, 1987).…”
Section: Discussionmentioning
confidence: 95%
“…Similar analyses of echinoderm sperm flagella (33,56) and mussel gill cilia (34) have been performed. The central pair does not appear to rotate in these organisms (for imposed rotation in sea urchin sperm, see refs.…”
Section: Precision Of Central Apparatus Orientation In High and Low Cmentioning
confidence: 93%
“…However, the absence of rotation does not rule out the possibility that the central apparatus plays a role in specifying dynein activity on specific doublets. For example, in mussel gill cilia and echinoderm sperm the central apparatus maintains a specific orientation relative to the position of active sliding [Sale, 1986;Mohri et al, 1987;Satir and Matsuoka, 1989;Holwill and Satir, 1994]. In these cell types, specific interactions of the radial spokes with the central apparatus may positively or negatively control dynein activity by a switching mechanism that does not involve central apparatus rotation.…”
Section: Structural Analysis Of Central Pair and Radial Spoke Functionmentioning
confidence: 99%